Fluoride Toxicity Limit—Can the Element Exert a Positive Effect on Plants? - Zbigniew Jarosz (MDPI AG, 2021)
The problem of fluoride toxicity to living organisms is the subject of many studies. Its effect, not always toxic, on the human organism has been well documented. However, although the phytotoxicity of the element has been proved, this issue is still being investigated. It seems to be still relevant due to the progressive pollution of the environment and fluoridation of water. Assuming that the source of food for humans is plants, the content of fluoride in fruits and vegetables is important for human health. In the available literature, fluoride has been demonstrated to be phytotoxic at the level of cell transformations, biometric plant parameters, development of resistance, and biochemical processes in plants. However, several studies have provided information on improvement of certain plant parameters, e.g., the length of roots or shoots, caused by low fluoride doses and improvement of respiratory indices. The aim of this study was to analyze changes caused in plants by exposure to fluoride and to determine its beneficial effects based on the latest literature reports. It was based on the latest knowledge from the last 8 years. Attempts were made to compare earlier research results with contemporary items. In conclusion, the analysis has shown that, although some sources provide information on the positive effect of small fluoride doses, the impact of this element requires further investigations, as has not been fully elucidated.